A Proposal for Expansion of the Medical Specialty of Rehabilitation Medicine. (November 2022) - Sivan, Manoj; Cirasanambati, Mahesh; Okirie, Elie; Jeddi, Faraz; Smith, Matthew; Basu, Bhaskar; Watve, Sachin; Bose, Renjith; Balakrishnan, Sudha; Salawu, Abayomi; Jagatsinh, Yogendra; Williams, Vicki; et al.
The workforce of the medical specialty of Rehabilitation Medicine (RM) in the UK is 10 times less than the European average for the specialty of Physical and Rehabilitation Medicine (PRM). This can be explained partly by the difference in the scope of practice within the specialty between the UK and other European countries and USA. This opinion paper aims to compare the rehabilitation needs in chronic medical conditions and compare the scope of practice between countries within Europe and other regions of the world. The potential advantages of a broader remit specialty to improve rehabilitation care for patients by involving rehabilitation physicians in various medical conditions is explored. Recommendations have been put forward in the Rehabilitation Medicine Expansion Proposal (RMEP), which is likely to make the medical specialty of RM/ PRM more satisfying for the doctors working in the specialty and a more attractive career choice for those entering training in the specialty. There is a need for an international universal framework for the scope of the specialty to have a greater impact on improving the lives of those with chronic medical conditions.